Particle Number of Aerosol in Specific Conditions of Biotechnology Laboratory Cleanroom - Junga, Petr; Trávníček, Petr; Vítěz, Tomáš; Machů, Gabrielle; Ružbarský, Juraj (MDPI AG (Multidisciplinary Digital Publishing Institute-MDPI), 2023)
This paper presents the results of experimental measurements of the number of aerosol particles in cleanroom air of a biotechnology laboratory for DNA analysis. The aerosol content in the air can harm the accuracy of any analysis performed. The experimental measurements demonstrate compliance with the ISO cleanroom requirements for class 7. The indoor environment of the investigated biotechnology laboratory cleanroom can be classified as ISO cleanroom class 8. The particle count values depend on the month in which the measurement is made. The location of the measurement site, on the other hand, does not have too much influence. Our results showed that the values of particle number in the laboratory ranged from 325,965 to 2,740,877 pc/m3 for particles of 0.5 μm and more. From these measurements, it can be concluded that the biotechnology laboratory premises were not very suitable locations to perform for the intended DNA tests since microbiological contamination had the capacity to distort the results of these tests. As such, the authors propose several strategies to improve the current situation. These strategies are based on changing the laboratory work organization and cleaning methodology. In addition, the monitoring of particles with a size of 5 µm or more is recommended.
Keywords: cleanroom; particulate contamination; aerosol; filtration